Pengaruh Metode Pembelajaran, Motivasi Belajar dan Lingkungan Sekolah terhadap Hasil Belajar Akuntansi Kelas X di SMK N 1 Sutera Kabupaten Pesisir Selatan Tahun Ajaran 2021/2022 - Yulia Sarita Gusrel; Nora Susanti; Wati Wati (STKIP PGRI Sumatera Barat, 2022)
This study aims to analyze: 1) To determine the effect of learning methods on the learning outcomes of class X accounting students at SMK N 1 Sutera. 2) To determine the effect of learning motivation on the learning outcomes of class X accounting students at SMK Negeri 1 Sutera. 3) To determine the effect of the school environment on the learning outcomes of class X accounting students at SMK Negeri 1 Sutera. 4) To determine the effect of learning methods, learning motivation and school environment simultaneously affect the learning outcomes of class X accounting students at SMK Negeri 1 Sutera. This type of research is associative and descriptive. The population of this research is accounting students of class X at SMK Negeri 1 Sutera totaling 101 people. The sampling technique used is proportional random sampling with a sample size of 81 people. Data analysis was assisted by SPSS version 15 and eviews version 8. The results of this study indicate that: 1) Learning methods have a positive and significant effect on student learning outcomes. Learning motivation has a positive and significant effect on student learning outcomes. The school environment has a positive and significant effect on learning outcomes. There is a simultaneous influence of learning methods, learning motivation and school environment on learning outcomes, so it can be concluded that Hypothesis 4 is accepted which means there is an influence of learning methods (X1), learning motivation (X2) and school environment (X3). Based on the results of this study, the authors suggest that teachers can provide varied learning methods and make students not bored, suggest students to further increase student learning motivation, it is hoped that in learning, especially in completing the tasks given by the teacher, it should be done faster and not negligently as well as the environment. a clean and good school to take part in learning because the school environment is very important for the learning process.